Free Tax Clinic for the Public and Microbusiness Owners - Suryani Suryani (Advances in Community Services Research, 2026)
Purpose: This study evaluates the strategic role of free tax clinics in enhancing fiscal literacy, tax compliance, and access to fiscal services among low-income individuals and microentrepreneurs, with particular attention to their contribution to fiscal justice and economic empowerment in developing countries, especially Indonesia. Research Method: A Systematic Literature Review (SLR) was conducted using academic articles and best-practice reports from international and national sources related to tax clinics, financial literacy, tax compliance, and MSME empowerment. The selected literature was analyzed thematically to identify key contributions, implementation patterns, and challenges. Results and Discussion: Free tax clinics improve taxpayers’ understanding, access to fiscal incentives, and self-reporting capacity, particularly among MSMEs. Their effectiveness is strengthened by multistakeholder collaboration and integrated educational and community-based approaches. However, implementation remains constrained by low financial literacy, limited human resources, and cultural barriers. Implications: Policymakers should expand inclusive, evidence-based, and sustainable community tax services while strengthening public participation. Further research should empirically assess their long-term impacts. Originality: This study integrates fiscal literacy, tax access, compliance, and community empowerment into a unified framework for examining free tax clinics in developing-country contexts.